Determination of Crop Growing Period in Arid and Semi-arid Regions of Rajasthan - Rao, A S; Ramakrishna, Y S; Venkateswarlu, J (Annals of Arid Zone, 2016)
Simple criteria has been used for determination or Crop Orowing Period (COP) in arid/semi-arid regions of Rajasthan, based on information about soils, crop water requirement and assured rainfall of the region. Through the soil-water budgeting of long term rainfall in relation to crop water requirement, the assured COP at selected locations of Rajasthan was worked out using a computer programme. The assured COP thus analysed varied from 3 to 13 weeks under shallow soils and from 5 to 15 weeks under deep soils. A test analysis of COP- pearl millet grain yield relationship for the arid region of Jodhpur district is also presented.